2007
DOI: 10.1038/sj.mt.6300143
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery in a Friedreich's Ataxia Mouse Model by Frataxin Gene Transfer Using an HSV-1 Amplicon Vector

Abstract: There is currently no effective treatment for Friedreich's ataxia (FA), the most common of the hereditary ataxias. The disease is caused by mutations in FRDA that drastically reduce expression levels of the mitochondrial protein frataxin. In FA animal models, a key difficulty is obtaining the precise levels of frataxin expression in the appropriate tissues to provoke pathology without early lethality. To develop strategies to circumvent these problems, conditional frataxin transgenic mice have been generated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…We have previously demonstrated that viral vector-mediated expression of frataxin can rescue oxidative stress hypersensitivity of FRDA patient fibroblasts 1 and the neurological deficit in a mouse FRDA model. 3 Nevertheless, permanent correction of such inherited disorders in patients will require a sustained level of expression from the therapeutic transgene, a known difficulty in many viral vectors. A unique property of herpesvirus amplicon vectors is that they are capable of transporting very large transgenes such as whole genomic loci.…”
Section: Long-term Persistence Of Genomic Frataxin Vectormentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that viral vector-mediated expression of frataxin can rescue oxidative stress hypersensitivity of FRDA patient fibroblasts 1 and the neurological deficit in a mouse FRDA model. 3 Nevertheless, permanent correction of such inherited disorders in patients will require a sustained level of expression from the therapeutic transgene, a known difficulty in many viral vectors. A unique property of herpesvirus amplicon vectors is that they are capable of transporting very large transgenes such as whole genomic loci.…”
Section: Long-term Persistence Of Genomic Frataxin Vectormentioning
confidence: 99%
“…3 In brief, 17-day-old embryos were removed from a pregnant female mouse and dissected in pre-chilled Hank's-buffered salt solution. After removal of the meninges, striatum and hippocampus, the intact cortices were cut into small pieces and then incubated in a 0.25% trypsin (Sigma, Madrid, Spain), 1 mg ml -1 DNaseI (Roche, Barcelona, Spain) solution in Hank's-buffered salt solution without calcium and magnesium for 15 min at 371C, with gentle shaking every 3-4 min.…”
Section: Primary Neuron Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant adenoassociated viral and lentiviral vectors expressing frataxin cDNA have been shown to partially correct sensitivity to oxidative stress in FRDA primary fibroblasts [26]. Two recent reports have demonstrated in both cellular and animal models that herpes simplex virus type 1 (HSV-1) amplicon vectors expressing either the entire FRDA genomic locus [27] or frataxin cDNA [28] can successfully restore normal phenotypes. Specifically, Gomez-Sebastian et al [27] found that FRDA patient primary fibroblasts transduced with HSV-1:FRDA have a restored response to oxidative stress.…”
Section: Frataxin Reduction Causes Frdamentioning
confidence: 98%
“…The observed cytotoxicity of such helper viruspackaged amplicon preparations in neuroscience research is often much lower than that portrayed for pure stocks of the helper virus for different reasons: first, since the majority of the virions are vector particles, the effective MOI of the helper virus is very low, whereas cytotoxicity assays of HSV-1 mutants are usually carried out at high MOI; additionally, the HSV-1 genome is less cytotoxic in postmitotic neuronal tissue in vivo than in cultured neurons or epithelial cell lines which are often used for such analysis. Nevertheless, the variability in the ratio between vector and helper particles is difficult to control with helper-dependent amplicon systems and careful standardization of packaging procedures [123] is required to yield amplicon samples with consistently high ratios of vector to helper [121,124] which have been suitable for high-efficiency neuronal gene transfer in proof of concept experiments in optogenetics [125][126][127][128] and gene therapy [129].…”
Section: Replication-defective Helper Virusesmentioning
confidence: 99%